Coping with exploitative labour market: a case of Sri Lankan migrants in Bahrain - Mohamed Idrees, Mohamed Aslam; Eid, Iyad Muhammad; Rokis, Rohaiza (IIUM Press, International Islamic University Malaysia, 2023)
This study is a detailed description of the experience of Sri Lankan migrant workers in Bahrain, exploring the labour market exploitation after arriving in Bahrain and coping strategies. These migrants’ labour market experiences show contrasting and negative experiences after arriving at their destinations. The qualitative research method was utilised, drawing descriptive analysis (thematic analysis technique) of compiling data through semi-structured interviews. Thirty in-depth interviews with Sri Lankan migrant workers, who stayed with their families in Bahrain for more than six months, were conducted using a purposive sampling technique. The study has identified negative experiences of relationships with employers and co-workers in which migrants went through a range of exploitations. The study revealed that the power exercised by employers and co-workers was the prominent cause behind this exploitation. The findings have confirmed that the foremost goal of migration, earning through productive employment, has collapsed due to wage exploitation. Finally, the study highlights acceptance of exploitation as a coping strategy that the migrants had adopted to endure with their exploitative labour market. The information explored on the exploitation of migrant workers in Bahrain enriches the literature with a new sociological and empirical study which provides new evidence about the serious challenges that they had faced.